2005
DOI: 10.1007/s10107-005-0600-9
|View full text |Cite
|
Sign up to set email alerts
|

Valid inequalities based on the interpolation procedure

Abstract: We study the interpolation procedure of , which generates cutting planes for general integer programs from facets of cyclic group polyhedra. This idea has recently been re-considered by Evans (2002) and Gomory, . We compare inequalities generated by this procedure with mixed-integer rounding (MIR) based inequalities discussed in Dash and Gunluk (2003). We first analyze and extend the shooting experiment described in Gomory, Johnson and Evans. We show that MIR based inequalities dominate inequalities generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 13 publications
3
15
0
Order By: Relevance
“…The outcome is that Gomory mixed-integer cuts play a very special role among subadditive cuts, in that they typically produce, alone, a lower bound increase which is comparable to that obtained when the whole family of cuts is considered. This result confirms the theoretical findings of Dash and Gunluk [7], who showed that interpolated subadditive cuts are dominated by Gomory mixed-integer cuts in a probabilistic sense, as well as the computational experience of Cornuejols, Li and Vandenbussche [5] on the subfamily of k-cuts. Some interesting directions of work are finally addressed in Section 6.…”
Section: Introductionsupporting
confidence: 90%
See 4 more Smart Citations
“…The outcome is that Gomory mixed-integer cuts play a very special role among subadditive cuts, in that they typically produce, alone, a lower bound increase which is comparable to that obtained when the whole family of cuts is considered. This result confirms the theoretical findings of Dash and Gunluk [7], who showed that interpolated subadditive cuts are dominated by Gomory mixed-integer cuts in a probabilistic sense, as well as the computational experience of Cornuejols, Li and Vandenbussche [5] on the subfamily of k-cuts. Some interesting directions of work are finally addressed in Section 6.…”
Section: Introductionsupporting
confidence: 90%
“…A key observation at this point is that, being k ideal, the actual value of g(·) outside the sample points i/k is immaterial, since g(·) only needs to be evaluated on these sample points when computing the coefficients in (7). Therefore, the interpolation procedure does not actually restrict the space of the possible subadditive functions-as it would be the case for a different choice of k. As a consequence, we can exactly rephrase g-SEP as the following LP:…”
Section: Cuts From Subadditive Functionsmentioning
confidence: 99%
See 3 more Smart Citations